Does serum uric acid to high-density lipoprotein cholesterol ratio predict coronary slow flow? (Annals of Medical Research, 2021)
Aim: Several studies have found a correlation between coronary slow flow (CSF) and low serum high-density lipoprotein cholesterol (HDL-C) levels or high serum uric acid levels. The present study aimed to evaluate whether serum uric acid to HDL-C ratio predicts CSF.Material and Methods: The experimental (CSF) group included 91 patients (40 females, 51 males, mean age: 52±9) who had angiographically normal coronary arteries but had slow flow in one or more coronary arteries. The control group included 96 patients (57 females, 39 males, mean age: 50±9) with normal coronary anatomy and without slow flow. The uric acid to HDL-C ratio was calculated for the two groups and compared.Results: The HDL-C levels of the CSF group (37±8 mg/dL) were significantly lower compared to the controls (49±10 mg/dL, p0.001), whereas serum uric acid levels (5.33±0.97 mg/dL) and uric acid to HDL-C ratio (0.14±0.03) of the CSF group were significantly higher compared to the controls (4.37±0.88 mg/dL and 0.09±0.02, p0.001 and p4.64 mg/dL uric acid and >0.119 % uric acid to HDL-C ratio had a sensitivity of 81% and 85% and specificity of 76% and 80% for determination of CSF, respectively (AUC=0.850, 95% CI: 0.792 - 0.908 and AUC=0.890, 95% CI: 0.841 - 0.940,respectively).Spearman's correlation test has been performed and a significant positive correlation has been detected between the uric acid to HDL-C ratio and the mean thrombolysis in myocardial infarction (TIMI) frame count (r=0.62, p0.001).Conclusion: In this study, higher uric acid to HDL-C ratio values of the CSF group was found compared to the control group. Furthermore, uric acid to HDL-C ratio performed better than serum uric acid levels in predicting CSF.
Keywords: Atherosclerosis; coronary slow-flow; high-density lipoprotein cholesterol; uric acid; uric acid to high-density lipoprotein cholesterol ratio